Fundamentals of abstract algebra - Malik, D.S (International series in pure and applied mathematics, 1997)
This new addition to the International Series in Pure and Applied Mathematics is for the two-term advanced undergraduate course in abstract algebra. Each chapter consists of definitions, theorems, proofs, and corollaries. There are also numerous examples that help illustrate the concepts. A unique feature of this text is the worked-out exercises that appear after every section. These worked-out exercises provide techniques of problem solving for students. Sprinkled throughout the text are comments dealing with the historical development of abstract algebra as well as profiles of notable mathematicians. Special topics, such as algebraic varieties, matrix rings, and Noetherian and Artinian rings, are also included for those instructors who want additional material.